Fire Risk Perception of Timber Buildings : Implications for the Responsibility of Designers - Menzemer, Leo Willem ; 0000-0001-5348-1520 (Springer Tracts in Civil Engineering, 2025)
Timber’s sustainability benefits make it an attractive construction material, but public concerns about fire safety remain a challenge. Many associate timber buildings with higher fire risks, particularly in taller structures, despite trusting regulations and professionals to ensure safety. This highlights a gap between public perception and technical knowledge. Designers have a professional responsibility to address these concerns through clear communication and transparent, appropriate risk mitigation strategies to ensure the safety of building occupants. Disappointing this responsibility can negatively impact people’s safety and lead to stigmatization of wooden building materials.